Budget and Procurement Monitoring in Nigeria : A Civil Society Perspective - Zovighian, Diane (World Bank, Washington, DC, 2015)
Can governments be held accountable for spending by citizen organizations? In this issue the author present the experience of two civil society organizations (CSOs) engaged in budget and procurement review and monitoring in Nigeria. In the Nigerian context, the preconditions for accountable citizen-state relations are underdeveloped. In particular, some of the building blocks of transparent and accountable public financial management systems are absent or dysfunctional. Lack of information and limited opportunities for citizens' engagement in government processes have resulted in high levels of mistrust between citizens and government. Despite these challenges, there are people and groups, in both government and civil society, who have taken bold steps to ensure greater transparency and accountability in the planning and management of public resources. For example, networks of CSOs working in the area of procurement oversight have started demanding information on procurement bids. The World Bank civil society fund provides financial and technical support to CSOs aimed at improving their capacity and effectiveness to engage in reform and policy processes. Given the World Bank's broader focus on governance reforms, a particular emphasis has been placed on supporting CSO engagement in monitoring the use of public resources, including budget and procurement processes and the delivery of public assets and services. This note features interviews with two civil society fund (CSF) grantees. The first is with Amy Oyekunle, the executive director and manager of the CSF grant at the Kudirat Initiative for Democracy (KIND), and the second with Nkem Ilo, manager of the CSF grant at the Public and Private Development Centre (PPDC). The aim of these interviews is to look at how these organizations navigate the challenges of the Nigerian governance context and what they can realistically achieve with financial and technical support from the World Bank in this context.